2017
DOI: 10.1002/iub.1594
|View full text |Cite
|
Sign up to set email alerts
|

Lipocalin‐2 expression and serum levels as early predictors of type 2 diabetes mellitus in obese women

Abstract: Obesity and diabetes are increasing in epidemic proportions globally. Lipocalin-2 (LCN-2) is an inflammatory adipocytokine and obesity-related marker of low-grade inflammation. We aimed to investigate, for first time, the possible role of LCN-2 expression and serum levels in prediction of impaired glucose tolerance (IGT) and type 2 diabetes mellitus (T2DM) among obese Egyptian women. This study included 188 obese women and 180 controls. Obese women were subdivided into three subgroups according to their fastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
5
20
1
Order By: Relevance
“…This type of compensatory homeostatic response most probably accounts for the elevated circulating LCN2 levels that have been reported in obese and insulin-resistant states in mice and humans (De la Chesnaye et al, 2015;Wang et al, 2007Wang et al, , 2018Zhang et al, 2008;Yan et al, 2007;Rashad et al, 2017;Garbacz et al, 2017). Indeed, we found elevated circulating LCN2 levels in obese, prediabetic patients that correlate with BMI and insulin resistance but also β-cell function, indices of healthy glucose metabolism.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…This type of compensatory homeostatic response most probably accounts for the elevated circulating LCN2 levels that have been reported in obese and insulin-resistant states in mice and humans (De la Chesnaye et al, 2015;Wang et al, 2007Wang et al, , 2018Zhang et al, 2008;Yan et al, 2007;Rashad et al, 2017;Garbacz et al, 2017). Indeed, we found elevated circulating LCN2 levels in obese, prediabetic patients that correlate with BMI and insulin resistance but also β-cell function, indices of healthy glucose metabolism.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, normal-weight women whose LCN2 serum levels positively correlate with energy expenditure after a high-fat meal have improved fatty acid oxidation (Paton et al, 2013). Contrasting with this evidence, we note that elevated LCN2 serum levels have been associated with obesity and insulin resistance in mouse models and humans (Yan et al, 2007;Zhang et al, 2008;Wang et al, 2007;Kanaka-Gantenbein et al, 2008;Yoo et al, 2014;Rashad et al, 2017). Whether this increase in LCN2 levels is a cause or result of the metabolic dysregulation and whether it has an impact on disease progression have not been examined.…”
Section: Introductionmentioning
confidence: 86%
“…Moreover, elevated serum LCN2 level was shown to be associated with increased risk for T2DM. A recent study also indicated that LCN2 levels were elevated in obese women and could be used as an early predictor of T2DM [13]. Nevertheless, no significant association of LCN2 with HOMA-IR was indicated in non-diabetic obese women [14].…”
Section: Introductionmentioning
confidence: 99%
“…Postprandial serum levels of LCN2 were significantly increased after high‐fat meals; furthermore, this increase in postprandial LCN2 levels was accompanied by enhanced total energy expenditure, but only in normal‐weight individuals . In obese subjects, a decrease in postprandial LCN2 concentration occurred rather than an increase, and this decrease was generally attributed to higher levels of serum LCN2 under basal states in obesity . The underlying mechanisms that would account for these differences are unclear.…”
Section: Osteoblast‐derived Lcn2 As An Appetite Suppressormentioning
confidence: 99%
“…67 In obese subjects, a decrease in postprandial LCN2 concentration occurred rather than an increase, 67 and this decrease was generally attributed to higher levels of serum LCN2 under basal states in obesity. 68 The underlying mechanisms that would account for these differences are unclear. Whether Mechanistically, LCN2 can cross the blood-brain barrier, bind to the melanocortin 4 receptor (MC4R) in the paraventricular nucleus and ventromedial neurons of the hypothalamus, and use an established MC4R-dependent anorexia-promoting pathway to exert its anorexigenic function, thus decreasing body weight and fat mass and improving insulin sensitivity 10 (Figure 1).…”
Section: Osteoblast-derived Lcn2 As An Appetite Suppressormentioning
confidence: 99%